Ragam Bahasa Slang Pada Kata “Well” - Dimas Pramana Putra; Abian Rajiv Setyawan (Pusat Riset dan Inovasi Nasional, 2023)
In the 21st century, there are many uses of new and foreign language terms, not even a few of these language terms have become normalized or normalized by the community for use in everyday life. The problem contained in this study is that the use of the slang term